PENGEMBANGAN DIRI MENURUT PRINSIP AL-QURAN TERHADAP PENCAPAIAN SELF-ACTUALIZATION PERSPEKTIF ISLAM - Dandi dilayadi Saputra; Nurusshobah; Fitrah Sugiarto (LPPM STAI Muhammadiyah Probolinggo, 2025)
Abstract: This study explores the concept of self-development according to the principles of the Qur'an in the context of achieving self-actualization from an Islamic perspective. The primary focus of this research is to identify the principles in the Qur'an that support the self-development process and compare them with the self-actualization theory in Western psychology, specifically the theory proposed by Abraham Maslow. The method used is a literature review, analyzing Qur'anic exegesis, religious literature, and scholarly articles related to self-development theory and psychology. The research findings indicate that principles found in the Qur'an, such as the balance between spiritual, social, and personal aspects, play a crucial role in achieving self-actualization. Additionally, wise time management and strong faith are considered key elements in the self-development process in Islam. The implementation of Qur'anic principles in daily life, such as accepting criticism, time management, and positive social interactions, has proven effective in accelerating the achievement of self-actualization. This study also reveals the important role of the community in supporting individuals through social support, religious education, and social activities that shape character. The implications of this research emphasize the importance of applying Islamic principles in the lives of individuals and communities to create an environment that supports the achievement of one's fullest potential.